Surface and catalytic properties of nanosized CaO and Ca₃(PO₄)₂ extracted from natural resources - Thakur, Samriti (My University, 2021)
The work presented in this thesis enlightens the significance of naturally derived nanomaterials for their intended use in catalytic and photocatalytic activities (removal of organic pollutants). Main emphasis has been given to the extraction of calcium oxide from natural resources such as mollusc shells, waste chicken shells and cuttlefish bone, their characterization and application in adsorption and catalytic activitiesLiterature review, research gap, objectives, experimental section and characterization techniques are also incorporated. Nano structuring and surface functionalization of industrially important Calcium Oxide (CaO) material has broad spectrum applications in daily civic life. In this context, cubical shape CaO nanoparticles are extracted via an eco-friendly green approach from dead mollusc shells collected from sea beaches. The surface structural morphology of as-prepared catalyst is thoroughly characterized by XRD, DLS particle size, SEM, TEM-EDS, TGA, TPD, BET surface area (80 m2g-1) analysis, adsorption and electro-kinetic (zeta potential/point of zero charge) properties etc. measurement. Practical applications of this cubic nano crystal (lattice constant 12.51 Å and size 60-80 nm) for adsorption removal of toxic neutral red dye and catalytic activity for transesterification are systematically studied relative to commercial CaO particles under similar experimental conditions. Influential factors responsible for optimum dye adsorption isotherms, kinetics/thermodynamics of catalytic activity, stability and reusability/leaching are properly investigated in correlation with its observed crystal structural and physicochemical properties. Calcium oxide (CaO) is a promising sorbent, easily available and extractable from natural resources. The lattice strain and crystallite size for annealed (900 °C) nanospheres were assessed by W-H analysis from powder XRD data and the outcomes were found in good agreement with TEM results (40-50 nm). The present work reports the proficiency of CaO nanospheres towards removal of cationic (Brilliant Green) and anionic (Phenol Red) dye individually and their binary mixture as compared to monetarily available CaO. Adsorption studies in binary system showed that the extracted CaO showed higher adsorption (98%) of Brilliant Green (BG) than Phenol Red (PR) which is 78%, where strong electrostatic interactions played a significant role. CaO 3D nano flowers have been synthesized by time growth morphological evaluation from bud-to-blossom using dumped egg shells. A comparative study between commercially available calcium oxide and synthesized CaO nano flowers for adsorptive removal of used engine oil and aldol condensation was conducted. The average size distribution calculated using W-H analysis (1.28-1.38 µm) and morphological studies (1.26-1.30 µm) were in good agreement. The CaOnsf showed higher adsorption activity for spill oil remediation by dispersion-adsorption method with an extent of separation capacity upto 18 times its weight (18.31 gg-1 of CaOnsf) in comparison to CaOcm (8.4 gg-1). The as-synthesized nano flowers displayed excellent catalytic activity for aldol condensation between acetophenone and benzaldehyde. The nano flowers comprising of petals, are formed from many irregular elongated nanospheres. Higher surface area availability leads to higher catalytic activity for production of chalcone with a yield of about 76.3%. This study paves a way for development of CaO based 3D nanostructures, possessing higher adsorption efficiency for oil and an efficient catalyst for base catalysed reactions. Hierarchical Calcium Phosphate (CaP) nano flowers derived from cuttle fish bone was prepared using hydrothermal method. The CaP-TiO2 (1%) nanocomposite was prepared by in-situ method retaining CaP architecture. Sono-photocatalytic approach was applied for efficiently removal of environmental pollutants Bisphenol A and Rose Bengal dye (RB). CaP-TiO2 shows the best sono-photocatalytic performance for BPA (89%) and Rose Bengal (83%) degradation in comparison to CaP (BPA (76%) and Rose Bengal (69%)). Combination of both ultrasonic radiations and UV light irradiation increased radical generation which led to enhanced degradation efficiency. The degradation pathways for both BPA and RB dye are also given. CaO nanoparticles were synthesized using cuttlefish bone extract. Photocatalytic degradation of Paracetamol (PCM) and Fluconazole (FCZ), an analgesic drug has been investigated using CaO-TiO2 as a photocatalyst under UV light. Using CaO-TiO2 nanoparticles, much faster photodegradation of paracetamol and effective mineralization occurred, more than 90% of paracetamol was degraded under UV irradiation. Changes in pH values affected the adsorption and the photodegradation of Paracetamol. pH 9.0 is found to be the optimum for the photodegradation of paracetamol. The results showed that CaO-TiO2 is also effective in removal of fluconazole upto 84% than the bare CaO. All degradation kinetics was fitted to the pseudo-first-order model. A probable degradation pathway for paracetamol and fluconazole degradation was proposed based on liquid chromatography mass spectrometry analysis of degraded fragments.
Keywords: CaO; Natural resources; egg shells; transesterification; green synthesis